Synthesis and Biological Evaluation of Indole‐2‐carbohydrazide Derivatives as Anticancer Agents with Anti‐angiogenic and Antiproliferative Activities. (23rd May 2018) - Zhang, Jianqiang; Liu, Tongyang; Chen, Mei; Liu, Feifei; Liu, Xingyuan; Zhang, Jihong; Lin, Jun; Jin, Yi
Abstract: A novel series of indole‐2‐carbohydrazide derivatives were synthesized, characterized, and evaluated for their antiproliferative activities against two cancer cell lines, HCT116 and SW480, and a normal human fetal lung fibroblast cell line, MRC‐5. Among this series, compound24 f displayed potent cytotoxic activities in vitro against HCT116 and SW480 cell lines with GI50 values of 8.1 and 7.9 μm, respectively, and was inactive against MRC‐5 cells. The newly synthesized compounds were also evaluated for anti‐angiogenesis capabilities by chick chorioallantoic membrane, human umbilical vein endothelial cell (HUVEC) migration, and endothelial microtubule formation assays. Moreover, the effects of24 f on the vascular endothelial growth factor receptor‐2 and the signaling pathway in HUVECs indicated that this compound inhibits VEGFR‐2 and its downstream related proteins. These results indicate that compound24 f, as well as the other derivatives, are promising inhibitors of angiogenesis. Abstract : Stop the supply : A novel series of indole‐2‐carbohydrazide derivatives were synthesized, characterized, and evaluated for their antiproliferative activities. One of these derivatives, compound24 f, was evaluated for anti‐angiogenesis activity by chick chorioallantoic membrane, human umbilical vein endothelial cell migration, and endothelial microtubule formation assays. The results indicate that24 f is a promising inhibitor of angiogenesis.